Systemic loxoscelism in an epileptic patient. - Pichardo-Rodriguez, R. (2020)
Loxoscelism is the clinical problem produced by the bite of a spider of the genus Loxosceles. The most severe presentation is systemic loxoscelism that can compromise the patient’s life if itis not diagnosed and treated in time. There are no reports about how it presents in patients with an epilepsy diagnosis. We present the case of a 28-year old male patient, with a prior history of epilepsy in treatment with anticonvulsants. He developed systemic loxoscelism after a spider bite in the posterior middle third of the right arm. However, the patient did not develop seizures despite the unfavourable course of his clinical symptoms.